(untitled) (Mutah Journal of Humanities and Social Sciences (MJHSS), 2023)
This study aimed to identify the role of integrated reports in promoting social responsibility accountability of Jordanian banks listed in Amman Stock Exchange. Integrated reports consist of financial performance, governance report, environmental and social performance, strategic performance, and disclosure. The objectives of the study include the following: the descriptive analytical approach and social surveys, as a study strategy. A questionnaires was designed and distributed to (80) participants. However, (80) questionnaires were retrieved. The sample of the study involves financial managers and directors of the Internal Audit Department, the Department of Risk Directorate, the Compliance Department, and the Department of Development and Business Follow-up of the Jordanian Banks listed in Amman Stock Exchange (ASE) from (16) banks. In addition, financial reports were used to collect data on financial performance with its indicators, including return rate on investment and return rate on shareholders equity, for the period (2009-2018). The study used the Statistical Analysis Program (SPSS) to analyze that dara. One of the most important findings of the study is the impact of integrated reports in promoting social responsibility accounting of Jordanian banks listed in Amman Stock Exchange. The study showed that the governance report, environmental and social performance, strategic performance, and disclosure all affect social responsibility accounting, whereas, financial performance does not affect social responsibility accounting.